Effect of blood storage on electrolyte levels - Namjoshi, Abha; Namjoshi, Abha; Bhatia, Geeta M.; Chaudhari, Aparna S.; Chaudhari, Aparna S.; Trimbake, Sangeeta; Trimbake, Sangeeta (International Journal of Research in Medical Sciences, 2021)
Background: Blood transfusion can be an immediate life saving measure in several acute conditions such as hemorrhage and anemia. However, various post transfusion complications are observed in patients which may be associated with the storage conditions of the collected blood. Electrolytes play a major role in maintaining homeostasis within the cells. Potassium is the most important extracellular cation responsible for maintenance of the cell integrity. Prolonged and improper storage of blood can lead to leakage of electrolytes, thus changing the cell morphology. This can adversely affect the patients who receive such blood. This study helps us analyze the effect of blood storage on electrolyte levels. Methods: For the study, 10ml of blood was collected from 30 blood bags containing CPDA-1 at the time of blood donation from 30 different volunteers. This blood containing the CPDA-1 was divided into 5 parts of 2ml and each 2ml sample was stored in plain bulbs. All the samples were stored at 4°C. Samples were tested to check for changes in the electrolyte (Na+, K+, Cl-) levels on day 0, 3, 7, 14 and 21. ANOVA was used to calculate the variance in the electrolyte levels. Results: Average sodium level on day 0 was 152.9±3.8 mEq/l. There was a significant decrease and it was measured at 139.5±4.8 mEq/l on day 21. Average potassium level on day 0 was 4.2±0.4 mEq/l. A significant spike was observed in potassium levels. The final reading of potassium level on day 21 was 15.2±0.7 mEq/l. Average chloride level on day 0 was 71.9±6.6 mEq/l which significantly declined to 67±5.9 mEq/l. Conclusions: Though blood is stored in proper conditions, a biochemical change occurs within the cells due to prolonged storage and thus affects its viability.